If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2x * ln * x = 0 Multiply x * ln 3x + -2lnx * x = 0 Multiply lnx * x 3x + -2lnx2 = 0 Reorder the terms: -2lnx2 + 3x = 0 Solving -2lnx2 + 3x = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-3x' to each side of the equation. -2lnx2 + 3x + -3x = 0 + -3x Combine like terms: 3x + -3x = 0 -2lnx2 + 0 = 0 + -3x -2lnx2 = 0 + -3x Remove the zero: -2lnx2 = -3x Divide each side by '-2nx2'. l = 1.5n-1x-1 Simplifying l = 1.5n-1x-1
| 4+3p=19e | | -228=6(6v-2) | | 5x-1+y=0 | | solvex^2+2x-24=0 | | -9m=18.9 | | x-(-12)=7.3 | | 2x-3=23-2(x-5) | | 2x+5y=3x+2 | | 1=p-17 | | 4*(-6)= | | (2x-7)(3x+15)=0 | | 4x(-6)= | | %=3973*3215 | | 1/2p+7=3/4p+9 | | 3+2g=27 | | 5x=1-y | | 5(x+1)-2=4x+3 | | s^3-3s-2=0 | | 6(-3+-2x)(2+-1x)=0 | | 26+27=-39x-6 | | -5b-6-3b= | | 15-(4m+-5)=32 | | 10x-30=9x+11 | | 8+3x=0.5(16+6x) | | 5x-35=-5 | | 3=9+5y | | 3x-18=85 | | 5v^7=8 | | -l=n+5 | | 3(x+2)=4x+1 | | n/3-2=18 | | 13=48-x |